Influence of Income, Socialization, and Sanctions on Taxpayer Compliance to Pay PBB Tegal District - Ghea Dwi Rahmadiane (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2022)
This study aims to determine the effect of income, tax socialization, and tax sanctions on taxpayer compliance in paying Land and Building Tax in Bongkok Village, Kramat District, Tegal Regency. The data collection method used was interview and questionnaire techniques. The population used is 2702 taxpayers and the sample used is based on the results of the slovin formula of 96 respondents. The sample method used in this research is random sampling method. The data analysis method used in this research is multiple regression analysis method using SPSS analysis tool. The results showed that income, tax socialization, and tax sanctions had a positive and significant effect on taxpayer compliance in paying Land and Building Tax in Bongkok Village, Kramat District, Tegal Regency.